Nonlinear integral inequality in two independent variables. (1988) - Vaz, P. T.; Deo, S. G.
Abstract : In this note, the authors obtain a generalization of the integral inequality of Bihari [1] to a nonlinear inequality in two independent variables. With the aid of this inequality a bound for the solution of a nonlinear partial differential equation is established.